Strategies Of Bengkulu’s Culinary Msmes In Turning Creativity Into Business Success - Nurnaini Nurnaini; Sirwan Mayudi; Karona Cahya Susena; Kresnawati Kresnawati (Universitas Dehasen Bengkulu, 2026)
The Micro, Small, and Medium Enterprises (MSMEs) sector plays a strategic role in Indonesia’s national economic development, particularly in employment creation and improving community welfare. In Bengkulu Province, the culinary sector has become one of the fastest-growing subsectors within the creative economy. This study aims to analyze how culinary MSME entrepreneurs in Bengkulu transform creativity into business success, as well as to identify supporting and inhibiting factors. This research employs a qualitative descriptive approach, utilizing in-depth interviews, field observations, and document analysis involving 10 culinary MSME owners, Data wer analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results show that the creativity of Bengkulu’s culinary MSME actors is reflected in product innovation, packaging, and digital marketing strategies. The use of digital technologies, particularly social media and online marketplaces, has significantly expanded their market reach and increased sales. Key success factors include creativity, continuous innovation, market adaptability, and government support, while major challenges involve limited capital, managerial skills, and production infrastructure. The study concludes that creativity, when systematically managed and supported by a conducive business ecosystem, can significantly enhance the success of culinary MSMEs in Bengkulu. The findings are expected to serve as a reference for developing sustainable, locally based creative economy strategies.